The Role of Education and Attitudes in Cooking Fuel Choice: Evidence from two states in India - Gould, Carlos F. (Energy Sustain Dev, 2019)
Widespread adoption of clean cooking fuels is a necessary step toward reducing household air pollution and improving population health. Here we use large-scale surveys (10,000 households) from two Indian states, Kerala and Rajasthan, to examine how education and attitudes toward cooking associate with the adoption of liquefied petroleum gas (LPG), India’s most popular clean cooking fuel. We report three main results. First, education is a strong predictor of LPG adoption. Second, perceptions that LPG is good and affordable and progressive health-related perceptions are associated with LPG ownership. Third, and surprisingly, education does not predict positive attitudes toward clean cooking fuels. These results suggest that education leads to LPG adoption, but not through attitudinal changes. Further research should examine the mediators of the observed robust education-adoption association.